Subleukaemic acute myeloid leukaemia with myelodysplasia in a horse. (20th August 2018) - Miglio, A.; Pepe, M.; Felippe, M. J. B.; Antognoni, M. T.
Summary: Acute myeloid leukaemia (AML) is rarely reported in horses and myelodysplastic syndrome (MDS) has been described only in one case. Acute myeloid leukaemia is defined as the presence of at least 20% blasts in the marrow or blood. On the other hand, MDS is characterised by morphologic abnormalities in one or more cell lineages with hypercellular marrow and peripheral cytopenias due to ineffective haematopoiesis. We report a case of acute myelomonocytic leukaemia with myelodysplasia‐related features in a horse. A supposed diagnosis was based on abnormal morphology of circulating neoplastic cells and bone marrow cytology. A final diagnosis was made by using flow cytometry (FC) in conjunction with cytochemistry (CC) rarely reported in the haematopoietic neoplasms of the horse.